Chronic static stretching improves exercise performance - Kokkonen, J.; Nelson, A. G.; Eldredge, C.; Winchester, J. B. (Medicine & Science in Sports & Exercise, 2007)
Purpose: This study investigated the influence of static stretching exercises on specific exercise performances.